(untitled) (Global Journal of Science Frontier Research, 2022)
Warfarin is an oral anticoagulant drug that has a prolonged duration of action with delayed onset of action its chemical structure contains sodium atoms which may be hazardous to hypertensive patients To solve this problem sodium atom can be substituted with potassium or lithium atom which can help the patient to relieve hypertension in addition to it essential role as an anticoagulant Another advantage of this preparation is that it can be used as an antidote against digitalis toxicity but the warfarin interactions with other drugs are still the same as a cytochrome P450 inhibitor Warfarin reduces blood clotting by inactivating vitamin K epoxide reductase which activates vitamin K1 the main component in the blood clotting process Without sufficient vitamin K1 activation clotting factors II VII IX and X have decreased clotting ability The anticlotting protein C and protein S have also inhibited but to a lesser degree A few timesare required for the clotting process and these effects can take about five days Additionally because this process requires enzymes like VKORC1 patients who take warfarin with polymorphism of these enzymes can require adjustment as genetic factors should be taken into consideration thus may require lower doses